The effects of extending the school day in Latin America: a literature review - Ceballos, Fernando (2022)
A literature review is presented on the effects of school day extension programs implemented in various Latin American countries. According to their objects of interest, the studies are grouped into four types of impacts: a) school performance, b) academic and career paths, c) labor, and d) school organization and culture. A predominance of quantitative evaluations that analyzed the results in Mathematics and Language were identified, thus it was considered pertinent to broaden the knowledge search proposed from the programs. Other studies identified positive impacts on students' trajectories and their household economy; however, these results still need to be strengthened through similar studies in other contexts, which also inquire about the factors that explain these causes. Lastly, future studies should consider the particularities of each program in the search for their effects.